2012
DOI: 10.1186/1471-2229-12-239
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fruit ascorbic acid concentrations during ripening in high and low vitamin C tomato cultivars

Abstract: BackgroundTo gain insight into the regulation of fruit ascorbic acid (AsA) pool in tomatoes, a combination of metabolite analyses, non-labelled and radiolabelled substrate feeding experiments, enzyme activity measurements and gene expression studies were carried out in fruits of the ‘low-’ and ‘high-AsA’ tomato cultivars ‘Ailsa Craig’ and ‘Santorini’ respectively.ResultsThe two cultivars exhibited different profiles of total AsA (totAsA, AsA + dehydroascorbate) and AsA accumulation during ripening, but both di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 47 publications
9
108
0
1
Order By: Relevance
“…It is thus conceivable that the genes of the main biosynthetic pathway in the clusters 7 and 8 are functionally related to AsA accumulation only in the first stages of fruit development, when transcript abundance is still relevant. This inverse trend was well known and observed by different authors (Ioannidi et al 2009;Badejo et al 2012;Mellidou et al 2012). However, these observations support the idea that the biosynthesis and the maintenance of AsA pool rely on different mechanisms, including not only the main biosynthetic pathway (galactose) but also the alternative ones, the recycling and translocation processes.…”
Section: Gene Expression Analysissupporting
confidence: 68%
See 3 more Smart Citations
“…It is thus conceivable that the genes of the main biosynthetic pathway in the clusters 7 and 8 are functionally related to AsA accumulation only in the first stages of fruit development, when transcript abundance is still relevant. This inverse trend was well known and observed by different authors (Ioannidi et al 2009;Badejo et al 2012;Mellidou et al 2012). However, these observations support the idea that the biosynthesis and the maintenance of AsA pool rely on different mechanisms, including not only the main biosynthetic pathway (galactose) but also the alternative ones, the recycling and translocation processes.…”
Section: Gene Expression Analysissupporting
confidence: 68%
“…These genes could cooperate to favor the maintenance of AsA in later stages of ripening, while the contribution of the main biosynthetic pathway decreases. Indeed the presence of a MDHAR could play a fundamental role in the recycling of the ascorbate in later stages of ripening (Mellidou et al 2012). Concerning the three genes associated with the translocation, although previous feeding experiments revealed that translocation of AsA in fruit at red ripe stage is not relevant (Badejo et al 2012), the high expression detected for two of these three genes could underlie others mechanisms involved in the regulation/homeostasis of AsA pool in the mature fruit.…”
Section: Gene Expression Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Likewise, Yang et al (2011) showed that a higher AsA accumulation in fruit pulp of Citrus sinensis may be related to a higher expression of GME, GPP, GDH, and GLDH. However, Mellidou et al (2012) showed that only the expression of one ortologue of GGP correlates with a high AsA content found in a tomato cultivar characterized by fruits with a high AsA content.…”
Section: mentioning
confidence: 96%